1988
DOI: 10.1007/bf01655411
|View full text |Cite
|
Sign up to set email alerts
|

Secretory disturbance in hyperplastic parathyroid nodules of uremic hyperparathyroidism: Implication for parathyroid autotransplantation

Abstract: Pathophysiological characteristics of dispersed parathyroid cells were investigated in vitro with the principal aim of examining dominating hyperplastic parathyroid nodules in uremia. Ten large nodules were macroscopically dissected from the glands of 8 hypercalcemic patients with uremic hyperparathyroidism (HPT). Histologic examination revealed that the remaining parts of these glands were composed of a diffuse or slightly nodular parathyroid hyperplasia. Parathyroid hormone (PTH) concentrations were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 30 publications
6
65
1
Order By: Relevance
“…In addition to the increases in the mass of parathyroid tissue, another important mechanism responsible for 2HPT in uremia is probably the shift in the set-point for calcium-regulated PTH secretion. It has been reported that the control of PTH release by calcium is abnormal in parathyroid cells obtained from nodules (34). A similar abnormality was indicated in nodules with numerous oxyphil and transitional oxyphil cells in hyperplastic parathyroid due to uremia (35).…”
Section: Discussionmentioning
confidence: 58%
“…In addition to the increases in the mass of parathyroid tissue, another important mechanism responsible for 2HPT in uremia is probably the shift in the set-point for calcium-regulated PTH secretion. It has been reported that the control of PTH release by calcium is abnormal in parathyroid cells obtained from nodules (34). A similar abnormality was indicated in nodules with numerous oxyphil and transitional oxyphil cells in hyperplastic parathyroid due to uremia (35).…”
Section: Discussionmentioning
confidence: 58%
“…Through pathological evaluations, we also identify glands with diffuse hyperplasia, which we prefer for autotransplantation or to be left in the neck. It has been reported that patients with parathyroid nodular hyperplasia have higher rates of recurrence than those with diffuse hyperplasia after subtotal PTX or total PTX+AT (15). The cost of frozen section analysis is almost equal to that of IOPTH testing at our hospital.…”
Section: Discussionmentioning
confidence: 81%
“…In the preoperative course, identifying the localization of hyperplasic glands with 99m Tec sestamibi and ultrasonography may be insufficient (12)(13)(14)(15). The presence of aberrant localization or an ectopic gland observed through scintigraphy may affect the success of the exploration (16).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on PTH synthesis by parathyroid cells by evaluating the expression of PTH mRNA, and secretion by both in vivo study with dogs or rats and in vitro study of cell cultures [9][10][11][12][13][14][15][16][17][18][19] …”
Section: Discussionmentioning
confidence: 99%